PENGARUH HARGA, KUALITAS PRODUK, DAN MEREK TERHADAP MINAT BELI KONSUMEN - Sumaryanto, Puspita Arum Diastri, Rahayu Triastity & (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the significance of the influence of price,product quality, brand on consumer purchase intention. This type of research is a surveyon consumer Rainovel’s Distro in Surakarta. Sample as many as 100 people withaccidental sampling method. Data collection techniques used questionnaires,observations and documentation. Data analysis used multiple linear regression. Theresults showed that 1) Prices has a significant effect on consumer purchase intention 2)Product quality has a significant effect on consumer purchase intention 3) Brandsignificant effect on consumer purchase intentionKeywords: price, product quality, brand, purchase intention